Histories of Experience in the World of Lived Religion
XIII, 305 p. 3 illus. in color.
Keywords: 'At a historic moment, when religion shows all its social and political strength in various post-modern societies around our globe, this fascinating collection of studies from the Middle Ages to twentieth-century Europe demonstrates all the richness and innovative force of investigating individual and shared experiences when questioning the cultural, political and social place of religion in society. It also makes known in English the work of a series of Finnish historians elaborating together a pioneering vision of the notion of experience in the discipline of history.' - Piroska Nagy, Université du Québec à Montréal, Canada This open access book offers a theoretical introduction to the history of experience on three conceptual levels: everyday experience, experience as process, and experience as structure. Chapters apply 'experience' to empirical case studies, exploring how people have made and shared theirreligion through experience in history. This book understands experience as a simultaneously socially constructed and intimately personal process that connects individuals to communities and past to future, thereby forming structures that create and direct societies. It represents the crossroads of a new field of the history of experience, and an established tradition of the history of lived religion. Chapters offer a longue durée view from the fourteenth-century heretics, via experiences of miracle, madness, sickness, suffering, prayer, conversion and death, to the religious artisanship of soldiers in the Second World War frontlines. It concentrates on Northern Europe, but includes materials from Italy, France and United Kingdom.